Magnetic pyrite cinder as an efficient heterogeneous ozonation catalyst and synergetic effect of deposited Ce. (July 2016) - Wu, Deli; Liu, Ying; He, Hongping; Zhang, Yalei
Abstract : Heterogeneous catalytic ozonation was emerged to be a promising alternative in the mineralization of various persistent organic pollutants in recent decades. Magnetic pyrite cinder (PyC), which was employed as the catalyst in our investigation, was further deposited by Ce (Ce-PyC) to enhance its catalytic activity in the degradation of aqueous reactive black 5 (RB5). The results showed that additional 17.39%, 42.12% mineralization efficiency was obtained by O3 /PyC, O3 /Ce-PyC, respectively, in the degradation of RB5 compared to that of O3 alone under identical experimental condition. The reaction mechanism involved the enhanced mineralization of aqueous RB5 at the catalyst-solution interface via hydroxyl radicals produced by the reaction between O3 and catalyst surface. Besides surface hydroxyl, surface Ce(Ⅲ) was crucial for Ce-PyC in the enhanced generation of hydroxyl radicals. More surprisingly, it was found that both PyC and Ce-PyC could exert quite stable catalytic activity in a wide pH range from 3 to 10, which was supposed to be combined with inherently comprised various metal oxide, such as Fe2 O3, Fe3 O4, MnO2 and CuO. Ozone utilization evaluation demonstrated that PyC and Ce-PyC facilitated effective ozone decomposition, as ozone utilization efficiency (mgTOC/mgO3 ) of O3 /PyC and O3 /Ce-PyC increased 64.0%, 155.0%, respectively, compared to that of O3 alone. This investigation provided an effective alternative in the resource utilization of PyC, which was traditionally characterized as a waste material. Highlights: Pyrite cinder(PyC) exerted an efficient catalytic activity in the mineralization of RB5 by O3 . Optimized Ce deposition evidently enhanced the catalytic activity of PyC. PyC was found to keep quite stable catalytic activity in a wide pH range from 3 to 10. Surface hydroxyl and surface Ce(III) were crucial in the generation of hydroxyl radical.